INDUCTION ELICITATION OF CONTACT SENSITIVITY IN MICE DUE TO PROHAPTEN (Biological Sciences - PJSIR, 2002)
The prohaptenic status of abietic  acid ,  meth ylabietate, 3-methylcholanthrene  (3-Mc), 3-pentadecylphenol  (3-PDP), and 5-pentadecylresorcinol (5-PDR), was confirmed by partition coefficient studies and  conjugation  reactions  with  amino acids. The sensitizing effects observed on mou se skin showed activation of prohapten into hapten during the induction  and  elicitation  of the  contact  sensitization reaction s.